Effect of Human Serum Albumin on the Kinetics of 4-Methylumbelliferyl- ?-D-N-N -N" Triacetylchitotrioside Hydrolysis Catalyzed by Hen Egg White Lysozyme - Lissi-Gervaso, E; Calderon-Espinoza, C; Calderon-Espinoza, C; Abuin-Saccomano, E (2011)
The effect of human serum albumin (HSA) addition on the rate of hydrolysis of the synthetic substrate 4-methylumbelliferyl-?-D-N-N"-N" triacetylchitotrioside ((NAG)3-MUF) catalyzed by hen egg white lysozyme has been measured in aqueous solution (citrate buffer 50 mM pH = 5.2 at 37 °C). The presence ofHSAleads to a decrease in the rate of the process. The reaction follows a Michaelis-Menten mechanism under all the conditions employed. The catalytic rate constant decreases tenfold when the albumin concentration increases, while the Michaelis constant remains almost constant in the albumin concentration range employed. Ultracentrifugation experiments indicate that the main origin of the observed variation in the kinetic behavior is related to the existence of an HSA-lysozyme interaction. Interestingly, the dependence of the catalytic rate constant with albumin concentration parallels the decrease of the free enzyme concentration. We interpret these results in terms of the presence in the system of two enzyme populations; namely, the HSA associated enzyme which does not react and the free enzyme reacting as in the absence of albumin. Other factors such as association of the substrate to albumin or macromolecular crowding effects due to the presence of albumin are discarded. Theoretical modeling of the structure of the HSA-lysozyme complex shows that the Glu35 and Asp52 residues located in the active site of lysozyme are oriented toward the HSA surface. This conformation will inactivate lysozyme molecules bound to HSA. © 2011 Springer Science+Business Media, LLC.